AB1101 The development of a palatable, stable oral methotrexate solution. (12th June 2018) - Penton, J.-A.; Winslade, J.; Roberts, D.; Conroy, S.
Abstract : Background: Methotrexate is used in the treatment of Rheumatoid Arthritis, Juvenile Idiopathic Arthritis and other conditions such as Acute Lymphoblastic Leukaemia and psoriasis. It can be administered orally or by injection. With oral administration, methotrexate's bitter taste may not be masked, particularly when tablets are crushed to facilitate dosing in paediatrics or patients who have difficulty swallowing tablets. 1 This can lead to long term treatment adherence issues and inaccurate dosing, putting patients at risk of adverse reactions or inadequate efficacy. A palatable oral liquid presentation of methotrexate would facilitate more accurate dosing and potentially improve treatment adherence; however, methotrexate is difficult to formulate as an oral liquid due to taste, solubility and stability challenges. Despite these difficulties, a palatable, stable oral methotrexate solution has been developed. Objectives: To develop a palatable, stable, oral methotrexate solution, which complies with EU requirements for development of paediatric products, 2 to aid accurate dosing and treatment adherence. Methods: During each of two single-dose (10 mg and 2.5 mg) bioequivalence studies of the test 2 mg/ml methotrexate oral solution with licenced tablets, 24 healthy male subjects were asked to comment on the oral solution's taste, indicating whether it was: Bitter, Sour, Salty, Sweet, or No Obvious Taste and they could also leave a remark. In parallel to clinical studies, long term ICH stability studies at ambient conditions (25°C/60%RH) and in-use shelf life studies were conducted. Results: All subjects in the 10 mg dose study reported the oral solution as sweet tasting. One subject also reported an aftertaste and strange smell. In the 2.5 mg dose study, all subjects except one reported the solution as sweet tasting. The remaining subject reported a 'soothing' taste. One subject reported it was also sour and another reported an aftertaste. Two subjects additionally commented that they liked the taste. Both studies demonstrated bioequivalence and a similar safety profile between the oral solution and tablets. The stability studies illustrated that the oral methotrexate solution utilised in these clinical studies was stable at ambient conditions for up to 20 months, including a 3 months in-use period. The oral solution has recently been granted a European Union marketing authorisation and is the first methotrexate oral solution to be authorised for treatment of polyarthritic Juvenile Idiopathic Arthritis in Europe. Conclusions: A 2 mg/ml oral methotrexate solution, developed to improve treatment adherence and dose accuracy, is reported to have a palatable, sweet taste and can be stored long term at ambient conditions with a 3 months in-use period. References: [1] 1. Vrignaud S, et al. Int J Pharm 2015;487(1−2):270−3. [2] EMA/CHMP/QWP/805880/2012Rev. 2 Acknowledgements: The clinical studies were conducted at PAREXEL. The development work was conducted at Quay Pharmaceuticals. Disclosure of Interest: J.-A. Penton Employee of: Therakind Ltd, J. Winslade Shareholder of: Therakind Ltd, Employee of: Therakind Ltd, D. Roberts Employee of: Therakind Ltd, S. Conroy Shareholder of: Therakind Ltd, Employee of: Therakind Ltd